Fluid biomarkers of Alzheimer's disease in the Systolic Blood Pressure Intervention Trial: Developing topics. (7th December 2020) - Pajewski, Nicholas M; Elahi, Fanny M; Ix, Joachim H; Nasrallah, Ilya M; Reboussin, David M; Tamura, Manjula Kurella; Wright, Clinton B; Hinman, Jason; Miller, Lindsay M; Sudduth, Tiffany L; Wilcock, Donna M; Williamson, Jeff D
Abstract: Background: The Systolic Blood Pressure Intervention Trial (SPRINT) demonstrated that intensive treatment (systolic blood pressure (SBP) target <120 mm Hg) reduces the risk for mild cognitive impairment and slows the progression of white matter lesions detected via magnetic resonance imaging (MRI) as compared to standard treatment (SBP<140 mm Hg). However, it is unclear what pathway(s) mediate this effect. Method: We measured plasma beta‐amyloid 40 (Aβ40 ), beta‐amyloid 42 (Aβ42 ), total tau, and neurofilament light (NfL) at baseline and during follow‐up (median follow‐up = 3.8 years) in a subgroup of participants 60 years or older that also participated in SPRINT's MRI imaging substudy (N=542). We modeled changes in each AD biomarker using robust linear mixed models. Result: The average baseline age of this subgroup of SPRINT participants was 69.8 ± 7.1 (standard deviation) years; with a mean SBP of 138.2 ± 17.0 mm Hg; and 42.1% were female. At baseline, the strongest plasma biomarker correlations were with age (Spearman's rho = 0.27 for Aβ40 and 0.43 for NfL, both P<0.001) and estimated Glomerular Filtration Rate (eGFR; rho ranged from –0.21 for Aβ42 to ‐0.42 for NfL, all P<0.001). We observed larger increases in each AD biomarker for participants that experienced ≥30% decline in eGFR during follow‐up, which occurs more frequently with intensive treatment. There were no significant between‐group differences for Aβ40, Aβ42, or total tau, however intensive treatment was associated with larger increases in NfL during follow‐up (mean change per year (MCPY) = 2.6 pg/ml, 95% CI: 1.8‐3.3), as compared to standard treatment (MCPY = 1.6 pg/ml; 95% CI: 1.3‐1.8). This difference was explained by changes in eGFR (between‐group difference in MCPY adjusting for eGFR = 0.04 pg/ml; 95% CI: ‐0.76 ‐ 0.84). Conclusion: In this pilot study of SPRINT participants, after accounting for kidney function, intensive treatment was not associated with significant changes in fluid biomarkers of AD. Our results highlight the need for future studies of blood‐based AD biomarkers to account for renal function, especially within the context of hypertension and vascular disease.